MEDIA VISUAL PROMOSI PARIWISATA RELIGI DI KABUPATEN LOMBOK BARAT - Wiguna, I Wayan Indra; Artha, I Putu Yogi (Samvada : Jurnal Riset Komunikasi, Media, dan Public Relation, 2024)
West Lombok Regency is one of the tourism destination areas, because there are historical heritage buildings of temples and tombs. Both are used as religious tourism destinations. However, in reality, religious tourism destinations are not a priority tourism destination by tourists. Tour guides play an active role in promoting religious tourism in West Lombok Regency. The purpose of this research is to analyse the role of tour guide communication in promoting religious tourism in West Lombok Regency. This research is designed as descriptive qualitative research. Data were collected through observation, interviews, documentation. Data analysis uses data reduction, data verification. The results of the study revealed that the role of tour guide communication in promoting religious tourism in West Lombok Regency is to play an active role in introducing religious tourism, as a disseminator of information, as a communicator in explaining story telling and story nomic, and innovative disseminators to the community and government.